Evaluation of urinary tract infections in patients admitted in an intensive care unit (ICU) at Inkosi Albert Luthuli central (IALCH) hospital in Kwazulu-Natal, Durban: A retrospective cross-sectional study designed to determine the most prevalent pathogens of urinary tract infections. - Dlamini, Nqobile; S. Shangase (Student's Journal of Health Research Africa, 2025)
Background Urinary tract infections are among the most prevalent diseases in patients admitted to the Intensive Care Unit (ICU). ICU patients are at higher risk for UTIs due to factors such as indwelling urinary catheters, prolonged hospital stay, antibiotic use, immunocompromised, and underlying comorbidities like diabetes. Aim To identify the most prevalent isolated microorganisms causing UTIs in ICU patients with UTIs. To Assess Antimicrobial Susceptibility Patterns of isolated microorganisms. To analyse demographic information of patients with UTIs. Methodology This project was a retrospective quantitative study that looked at ICU patients admitted to IALCH. The study was a convenience non-probability study, which was done in an NHLS microbiology laboratory using standard urine culture and a VITEk-2 automated system. Results 270 positive urine specimens, the most common isolate was Escherichia coli (n=143; 53%), followed by Klebsiella pneumoniae subsp (n=40; 14.8%). Enterococcus faecalis (n=16; 6.0%) was the most common Gram-positive pathogen. E. coli showed significant resistance to Cefotaxime, ceftriaxone (31.4%), Gentamycin (10.4%), cefepime (6.3%) ,and piperacillin-tazobactam (3.5%). Among Gram-positive, E. faecalis showed 75% susceptibility. Conclusion E. coli was the most common isolate, accounting for 53% followed by Klebsiella pneumoniae subspp and E. faecalis in ICU patients admitted to IALCH. Notably, E. coli exhibited significant resistance to multiple antibiotics, including cefotaxim, ceftriaxone, gentamycin, cefepime, and piperacillin. In contrast, E. faecalis demonstrated 75% susceptibility to the tested antibiotics. E. faecalis was also most prevalent among the gram-positive, accounting for 6.0%. Vancomycin was found to be the most effective for E. faecalis. Ciprofloxacin was found to be the least effective, with a high rate of resistance for E. faecalis. This study also discovered that UTIs were more common in patients between the ages of 40-65 years, and the study showed that the most affected were females. Recommendations Future research should prioritize comprehensive data collection methods.